Transparent magnesium aluminate spinel ceramics obtained by one-step spark plasma reaction sintering of a sol-gel precursor powder. Issue 18 (15th September 2022) - Zarazúa-Villalobos, L.; Fantozzi, G.; Bonnefont, G.; Téllez-Jurado, L.; Balmori-Ramírez, H.
Abstract: Transparent magnesium aluminate spinel (MAS) was obtained by one-step spark plasma reaction-sintering (SPRS) of a nanosized sol-gel powder. The sol-gel powder was processed to obtain three powders as precursors materials with different characteristics. The first powder (HT0) was the as-synthesized sol-gel powder, comprising poorly crystallized boehmite and residual magnesium nitrate hexahydrate. The second powder (HT450) was obtained by calcination of the sol-gel powder at 450 °C to produce an incipient formation of MAS. The third powder (HT850) was calcined at 850 °C to produce spinel with low crystallinity. The powders were deagglomerated and then consolidated in one step using a spark plasma sintering (SPS) machine at temperatures ranging from 1260 to 1350 °C to suit their different properties. The one-step SPRS was achieved with relative densities up to 99.98 % and submicron-sized grains. However, transparent ceramics were obtained only with the HT450 and HT850 powders. The ceramic produced from the HT450 powder achieved a light transmittance of 71 % at λ = 1100 nm, Vickers hardness (HV) of 11.98 GPa, grain size of 604 nm, and relative density of 99.98 %. The ceramic produced from the HT850 powder consolidated by one-step SPRS at 1275 °C achieved a light transmittance of 71 %, HV of 12.71 GPa, grain size of 396 nm, and relative density (RD) of 99.90 %. The results showed that the HT450 powder had better sinterability, attributed to the higher reactivity of the partially reacted sol-gel particles used as precursors in this sample.